Hybrid Ceramics Cementation Protocols: Scope Review - Beltrami, Ícaro Menezes [UNESP]; de Lima, Cássia Cunha [UNESP]; do Nascimento, Camila Teixeira [UNESP]; Gonçalves, José Guilherme Pereira [UNESP]; Azarias, Josuel Siqueira [UNESP]; Bortoleto, Ana Laura Ferreira [UNESP]; Goiato, Marcelo Coelho [UNESP]; dos Santos, Daniela Micheline [UNESP] (Medicina Oral, S.L., 2024)
Background: Compared to high modulus repair materials such as zirconia and alumina, hybrid polymer-ceramic materials have lower stress concentrations in the tooth structure and bonding interface. The aim of this study is to evaluate viable cementation protocols through an integrative review and meta-analysis. Materal and Methods: This systematic review was based on the PRISMA criteria. An electronic search was carried out in seven databases: Web of Science, Embase, PubMed, Clinical Trials, Scopus, Cochrane, Periodicals of Capes. The following inclusion criteria were used: hybrid ceramics, surface treatment protocol and which union test was presented, discarding duplicate articles and studies that did not meet the inclusion criteria. The articles were analyzed and selected through the RayYan platform. Results: Of the 160 articles identified, 24 studies were included in this review. The materials used by the authors were the hybrid ceramics: Vita ENAMIC, LAVA ULTIMATE, Cerasmart, Shofu Block, and the possible surface treatment protocols presented involving the use of: HF, Alumina blasting with or without silica, Silane, Laser and adhesive. The tests were carried out at different times and concentrations of the analyzed materials. Conclusions: With the studies that were included in this review, it was possible to show that the corrosion made by HF continues to be the gold standard for the treatment of surfaces in hybrid ceramics.
Keywords: Bond Strength; Cementation; Hybrid ceramic